2019
DOI: 10.3345/kjp.2018.06835
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high fat dietary modification and nutritional status on the outcome of critically ill ventilated children: single-center study

Abstract: Background Ventilator dependency constitutes a major problem in the intensive care setting. Malnutrition is considered a major determinant of extubation failure, however, attention has been attracted to modulating carbon dioxide production through decreasing carbohydrate loading and increasing the percent of fat in enteral feeds. The detected interrelation between substrate oxidation and ventilation outcome became the base of several research to determine the appropriate composition of the nonprotein calories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In the literature, there are some evidences of a beneficial effect of a high-fat lowcarbohydrate diet in mechanically ventilated patients [52][53][54], since it was able to reduce PaCO 2 levels [52,53,55] and the time of mechanical ventilation [52,53].…”
Section: Low-carbohydrate Ketogenic Diets and Respiratory Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, there are some evidences of a beneficial effect of a high-fat lowcarbohydrate diet in mechanically ventilated patients [52][53][54], since it was able to reduce PaCO 2 levels [52,53,55] and the time of mechanical ventilation [52,53].…”
Section: Low-carbohydrate Ketogenic Diets and Respiratory Functionmentioning
confidence: 99%
“…These may be due to the impaired respiratory mechanics, increased airway resistance and impaired gas exchange [ 25 , 28 , 54 ], as well as obesity-related comorbidities [ 63 ], which appear to be directly related to the onset of complications and severe course of COVID-19. In particular, OSAS [ 38 ], metabolic syndrome, hypertension, Non-Alcoholic Fatty Liver Disease (NAFLD) and diabetes or insulin resistance have all shown to affect COVID-19 outcome negatively [ 55 , 56 , 57 , 58 ]. Finally, it should not be overlooked that obesity is associated with low chronic inflammation within a state of immunological dysfunction that can lead to increased risk of allergies [ 64 ] or ineffective response against infections [ 35 ] and vaccines [ 65 ].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Fat is a good source of nonprotein energy when it is necessary to provide high energy intake in a low volume of feedings [ 93 , 94 ]. For preterm infants with BPD, fat provides essential fatty acids and lipid soluble vitamins, and its oxidation produces less carbon dioxide [ 92 ].…”
Section: Nutritional Approach In the Prevention And Management Of Bpdmentioning
confidence: 99%
“…On the other hand, a study on 32 patients requiring mechanical ventilation reported no beneficial effects of a similar low-carbohydrate high-fat enteral nutrition (55.2% fat, 28.1% carbohydrate) in PaCO 2 levels during weaning from the ventilator, respect to a standard enteral nutrition (30% fat, 53.3% carbohydrate) ( 58 ). Another recent study on 51 critically ill ventilated children with pulmonary disease observed that the low-carbohydrate high-fat diet (30% carbohydrate, 50% fat) was effective in reducing carbon dioxide tension but did not reduce the duration or level of ventilatory support ( 59 ).…”
Section: Low-carbohydrate High-fat Diets Respiratory Failure and Mechanical Ventilationmentioning
confidence: 99%